The Effect of Reaction Training on Futsal Goalkeeper's Reaction Ability - Zahra Tias Salsabilla Gunawan; Adang Sudrazat; Rizal Ahmad Fauzi (Universitas Negeri Semarang, 2026)
The background of this research is based on the importance of the role of goalkeepers who are required to have a high reaction speed in responding to stimuli that come quickly and unexpectedly. The use of rugby football as a training medium gives the characteristics of irregular bounces. So that it can provide a more varied reaction stimulus for the goalkeeper in responding to the direction of the ball's arrival. This study aims to analyze the effect of reaski ball training using rugby ball media on improving the reaction ability of futsal goalkeepers. The research method used was quasi-experimental with a pretest-posttest design of one group. The population in this study is 10 UKM futsal goalkeeper athletes at the Sumedang Campus, with a sampling technique using purposive sampling. The instrument used is the Hand Touch Reaction Test to measure the reaction speed. Treatment in the form of reaction ball training using rugby balls was given for 4 weeks with a total of 12 meetings. Data analysis was carried out using a paired sample t-test at a significance level of 0.05. The results showed that the average reaction time decreased from 1.3840 seconds in the pretest to 1.1900 seconds in the posttest. In addition, a significance value of 0.000 (p ≤ 0.05) was obtained, indicating a significant difference between before and after treatment. Thus, it can be concluded that reaction ball training using rugby ball media has a significant influence on improving the reaction ability of futsal goalkeepers.